The role of TRIM family in metabolic associated fatty liver disease - Zhang, Jingyue; Zhang, Yingming; Ren, Ze; Yan, Dongmei; Li, Guiying (Frontiers in Endocrinology, 2023)
Metabolic associated fatty liver disease (MAFLD) ranks among the most prevalentcommon chronic liver conditions globallydiseases worldwide. At present, the mechanism of MAFLD has not been fully elucidated. Tripartite motif (TRIM) protein is a kind of protein with E3 ubiquitin ligase activity, which participates in highly diversified cell activities and processes. It not only plays an important role in innate immunity, but also participates in liver steatosis, insulin resistance and other processes. In this review, we focused on the role of TRIM family in metabolic associated fatty liver disease. We also introduced the structure and functions of TRIM proteins. We summarized the TRIM family's regulation involved in the occurrence and development of metabolic associated fatty liver disease, as well as insulin resistance. We deeply discussed the potential of TRIM proteins as targets for the treatment of metabolic associated fatty liver disease.